Моделювання фонемної структури лексем сучасної італійської мови - Близнюк, В. (Лексикографічний бюлетень, 2006)
The analysis of phonemic structures of lexemes in a modern Italian literary language is carried out. The structure of a word is regard as a canonical form. Inductive and deductive linguistic model is a real-life and theoretically possible canonical forms are compared.